(untitled) (Fiep Bulletin - online, 2013)
In the current world where we live science advances with rapidity and in the form of technology that if inserts in all the relations what it contributes to reformulate the complex relations most intrinsic and of the professional of the area of the health, in this case the physiotherapy. The objective of this study was to investigate the relation between the physiotherapy and the technoscience. The physiotherapy is perceived in a period of 40 years left to present formation characteristics technique. It passed to be understood as science, therefore, searched recital scientific to guide the practical clinic, becoming each more complex and varied time, increased at every moment of techniques and more efficient and accessible methods to the population. This development and transformation of physiotherapy have the techno as one of the main agents responsible for these changes. Ahead of this relation between the physiotherapy and the technoscience, one gives credit that the physiotherapy foments a bigger flow of scientific materials as well as the permanent intellectual reconstruction of the professional.